The American scene of Mary Overlie and the origin of the Six Viewpoints - Rinaldi, Miriam [UNESP] (Universidade do Estado de Santa Catarina, 2021)
To a greater or lesser degree, improvisation is an inherent element of the performing arts. However, the concepts that guide the construction of improvisation utterances reflect the values and concepts of their time. Six Viewpoints, an improvisation system articulated by Mary Overlie, was made public in 1978 and since then it has been consolidated and today participates in the formation of many artists in Brazil. Its origin, however, is not dissociated from its historical activities. In this biographical article, a connection between practice and public theory was sought, drawing some traces of the trajectory of the artist Mary Overlie from her childhood in Montana to 1980 in New York.
La escena estadounidense de Mary Overlie y el origen de lo Six Viewpoints
A cena americana de Mary Overlie 1 e a origem do Six Viewpoints
Keywords: Grand Union; Mabou Mines; Mary Overlie; Six Viewpoints